Non-ozone germicidal lamps for units of photochemical and photobiological action - Семенов, Анатолій Олексійович; Кожушко, Григорій Мефодійович; Баля, Лілія Вікторівна (Technology audit and production reserves, 2015)
The use of ultraviolet radiation is now becoming more and more important as the method of ultraviolet disinfection successfully destroys bacteria, fungi and viruses. The widespread use of UV radiation has become possible due to the expansion of the production of nomenclature of artificial light sources and increasing their efficiency. To this end, we have proposed the design of non-windowing germicidal lamp for UV irradiation of drinking water, air, surface and other liquids. As the basis of manufacturing technology it is proposed a construction of germicidal lamp, based on the following technical approach - invention, namely the transition from double capped fluorescent lamps to compact single-ended lamps. Design features of germicidal lamp, which limits the output of ozone in the environment, the following: the space between the discharge tube and the outer bulb is a gas filter, the spectral transmittance ratio adjusting pipe diameters and the partial pressure of oxygen and nitrogen. This radiation with a wavelength of 254 nm substantially not delayed by a gas filter, but the amount of ozone is reduced by 3-4 times, without exceeding the allowable limits. UV lamp is equipped with the necessary start-up equipment, which makes it possible to use in the domestic environment for the disinfection of drinking water and surfaces.